Educational Preparedness for Virtual Teaching and Learning during COVID-19 Lockdowns: Implication for Policy Innovation - Vuyiswa Sandrah Nyathi; Joyce Mathwasa (Randwick International of Education and Linguistics Science Journal, 2022)
The COVID 19, global pandemic that gripped Zimbabwe throughout 2020 and beyond posed numerous challenges across sectors, including education. As a result of this disaster, several state governments devised mitigation strategies to address challenges. In light of the foregoing, the paper intends to conduct a critical review of the education sector's emergency response to the COVID19 crisis using the document analysis method. It evaluates this strategy as an alternative approach for teaching and learning, revealing its strengths, challenges, and gaps, as well as fostering recommendations for its improvement for future policy innovations. The study used a desk-review methodology, also known as systematic inquiry, to critically evaluate the foundation of education and psychology using empirically researched secondary data (Mertens 2010), which has the potential to yield important new knowledge about virtual teaching and learning where distance is not a barrier. Up to now, a number of challenges and gaps have emerged in this emergency response, necessitating the development of effective and efficient catastrophe preparedness and response policies by educational policymakers. The study findings revealed that there are gaps in Zimbabwe's disaster legislation, which has an impact on the preparedness of education for it to embark in virtual learning during COVID-19 lockdown. The research also found that the education sector is not adequately prepared for disaster risk reduction in order to reduce the sector's vulnerability. The study suggests that intensive mobilization of resource and capacity building be undertaken so as to achieve the envisioned goals in education, with no child left behind.